1996
DOI: 10.1557/proc-453-253
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Lanthanide -Containing Halide-Modified Zinc Tellurite Glasses

Abstract: As part of an ongoing investigation to characterize the properties and structure of zinc halide-tellurium oxide glasses, we report preliminary measurements of the optical properties of several Nd- and Er-doped tellurites. Measurements include florescence lifetimes and estimates of the theoretical radiative lifetimes (as obtained by traditional Judd-Ofelt analysis of optical absorption spectra) as well as phonon sideband studies sensitive to vibrational characteristics near the rare earth ion. The response of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It is known that although TeO 2 is a former, it alone does not have the ability to form glass easily [31,60]. Our results on the effect of reducing TeO 2 can be discussed in the light of results from previous works on ternary tellurite glasses where several elastic studies on ternary tellurite glasses with unaltered TeO 2 content have been reported.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is known that although TeO 2 is a former, it alone does not have the ability to form glass easily [31,60]. Our results on the effect of reducing TeO 2 can be discussed in the light of results from previous works on ternary tellurite glasses where several elastic studies on ternary tellurite glasses with unaltered TeO 2 content have been reported.…”
Section: Discussionsupporting
confidence: 57%
“…Binary zinctellurite glasses have been extensively studied [23][24][25][26][27] and can be considered as a choice for the superheavy optical flint glasses [17] due to its stable structure [1,17,[28][29][30][31]. Zinc atoms are suggested to play an important role in forming glass network and the fractions of ZnO in binary zinc-tellurite glass can strengthen the whole network structure due to its bridging oxygen (BO) ion [1].…”
Section: Introductionmentioning
confidence: 99%